An approach to interpreting restrictive spirometric pattern results in occupational settings - Tafuro, Federica; Corradi, Massimo (La Medicina del Lavoro, 2016)
Objectives: The aim of this review is to provide an updated overview of definition, epidemiology, diagnostic algorithm and occupational exposures related to abnormal restrictive spirometrical pattern (RSP) in order to improve the correct interpretation of spirometry test results by occupational healthcare providers. Methods: A review of the scientific English literature of the last 25 years was carried out with MEDLINE and related keywords [(restricti* AND spirometr*) AND occupational]. The first step analysis covered 40 studies and the second step the reference list. Results are presented in four major aims and subquestions. Results: A spirometrical pattern of reduced VC (Vital Capacity), together with a normal FEV1 (Forced Expiratory Volume in 1 Second)/VC ratio, is suggestive, though not diagnostic of restrictive ventilatory defect (RVD). The prevalence of RSP is high in some studies, comparable to obstructive pattern, and could be associated to chronic medical conditions (diabetes, congestive heart failure, obesity, hypertension) as well as to increased risk of mortality and lung cancer. In order to predict true restrictive defect [TLC-(Total Lung Capacity) <LLN (Lower Limit of Normality) gold-standard for diagnosing restrictive lung diseases (RLD)] from spirometrical data, mathematical models have been developed, but more studies in occupational setting are necessary to clarify the accuracy of such approaches in health surveillance programmes. Occupational exposures that may lead to restrictive impairments are inhaled inorganic dusts (silica, asbestos), organic dusts (mainly from hypersensitivity pneumonitis agents) and other inhaled agents (syntetic fibers and flavorings). Conclusions: For spirometric data reliability it is mandatory to perform appropriate pulmonary function tests and use updated interpretive criteria. A reliable interpretation permits early recognition of RSP and, when indicated, to report workers to second level exams (TLC, decreased diffusing capacity for carbon monoxide [DLco], chest imaging). The application of mathematical models to better predict a reduction in TLC from spirometric data in occupational settings is required in order to reduce excessive costs and useless exams in health surveillance programmes.